A comunidade escolar e interação com a reserva biológica Pinheiro Grosso em Barbacena-MG - Couto, Suelen Ferreira Matoso (2018)
The Brazilian Biological Reserves (REBIO), instituted by the National System of Nature Conservation Units (SNUC), are characterized as Protected Areas (PA) of Integral Protection (IP), it is considered the most restrictive protected areas of the System. However, these Conservation Units of Nature (UCs) established by law, under federal, state and especially municipal administration, often do not reach the objectives of its creation and also those established by SNUC. In Brazil, the creation, implementation and ma nagement of PA has direct link with Environmental Education (EA). The SNUC is responsible for the organization and the criteria definition of the Brazilian Conservation Units and defines EA as an instrument that can make it possible to reach the objectives related to social participation and nature conservation, including in IP Units. A REBIO Pinheiro Grosso, a municipal conservation unit located in the rural district of Pinheiro Grosso, Barbacena / Minas Gerais - Brasil has an important biological diversit y, located close to the Municipal School Coronel Camilo Gomes de Araújo. It is known that the interaction between this PA and the local school is considered fragile and sporadic. In order to understand the potentialities, the reasons for its creation and its socioenvironmental importance, in addition to understand the relationship between the Municipal School and the REBIO Pinheiro Grosso, these research aims to characterize and discuss the use of the Biological Reserve area; to investigate the existence of EA actions developed by the school, discussing if those actions interfere in the students' interaction with the Reserve, and finally, to analyze the environmental perception of students and the elementary school teachers of the Municipal School Coronel Camilo Gomes de Araújo in relation to the Biological Reserve. For the construction of the theoretical-empirical referential, interviews were carried out with teachers and students, as well as extensive bibliographical and documentary research. It was concluded that the municipality of Barbacena, responsible for the administration of the PA should make public the potentialities and ways of use of this area, as well as invest in a continuous and emancipatory educational programs, at the municipal schools. One of this potentialities is the presence of important remnant of Atlantic Forest and great relevance in the water production of the region. Students and teachers have shown a deep interest in developing school projects beyond the limits of the school, in order to improve the quality of life and integration with the surrounding natural space, in this sense, it is believed that the school community should seek partnerships with the Federal Institute of Minas Gerais campus Barbacena in order to propose participation in extension work involving the REBIO.